A tale of two taonga: mutualistic research and management of heritage landscapes on Codfish Island (Whenua Hou), Aotearoa New Zealand. Issue 1 (2nd January 2021) - Fischer, Johannes H.; Tucker, Brooke
ABSTRACT: Biological and cultural heritage features regularly coexist and overlap within landscapes, creating complex management challenges. Codfish Island (Whenua Hou), Aotearoa New Zealand, exemplifies such a landscape, containing cultural and biological taonga (treasures) of national and international importance. Here, the last breeding colony of the critically endangered Whenua Hou Diving Petrel ( Pelecanoides whenuahouensis ) exists within archaeological sites preserving a rich Māori history and the earliest documented European settlement in southern Aotearoa New Zealand. The proximity of the breeding habitat of an endangered species to significant cultural heritage previously led to competing stakeholder interests which limited research and effective management. We present a mutualistic approach to landscape management on Codfish Island, which has resulted in positive outcomes for archaeological research, cultural heritage management, biological research, and conservation management. Collaborations like this are applicable in other heritage rich landscapes. Our mutualistic approach also forms a foundation for future joint monitoring schemes and research, facilitating transparent and informed management of both tangible and intangible components of the landscape.